2006
DOI: 10.1590/s1517-83822006000300007
|View full text |Cite
|
Sign up to set email alerts
|

Virulence-associated characteristics of Enterococcus faecalis strains isolated from clinical sources

Abstract: Thirty-two clinical isolates of Enterococcus faecalis were screened for virulence factors. Twenty-four (75%) isolates produced hemolysin on Mueller-Hinton blood agar plates with sheep erythrocytes. However, the cell free heat-stable hemolysin was detected in all isolates (100%) of E. faecalis when grown in BHI-GA (BHI medium supplemented with 1% glucose and 0.03% L-arginine), but not in BHI broth alone. Twenty-four isolates (75%) produced caseinase and 23 (71.9%) lipase, but none of the isolates produced gelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 38 publications
5
18
0
Order By: Relevance
“…Hemagglutinating activity was negative in all (100%) E. faecalis isolates with sheep erythrocytes. Our results substantiate the findings of Furumura et al [30].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Hemagglutinating activity was negative in all (100%) E. faecalis isolates with sheep erythrocytes. Our results substantiate the findings of Furumura et al [30].…”
Section: Discussionsupporting
confidence: 94%
“…Casein hydrolysis was observed in 38 (73%) isolates of E. faecalis. Data does suggest that the gelatin hydrolyzing activity is different from caseinase and also supported previous findings (30). Sedgley et al [33] found that gelatinase gene (gelE) was detected in all endodontic isolates of E. faecalis while expressed gelatinase activity was observed in two thirds of the isolates.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…indicates its ability to attack host cell by degrading the membrane proteins and has been considered as one of the basic virulence pathway (Furumura et al, 2006). Our study again confirms the importance of this extracellular type of enzyme in V. paraheamolyticus with its dominance presence (11/17 or 64.7 % tested isolates).…”
Section: Resultssupporting
confidence: 82%
“…The enzyme is an extracellular zinc endopeptidase that plays a very significant role in bacterial pathogenesis by causing direct or indirect damage to host tissue thus facilitating microbial invasion and survival in the host (Alebouyeh et al, 2005;Furumura et al, 2006). The presence of these enzymes on E. coli isolates is a further confirmation of their potential to cause infections.…”
Section: Discussionmentioning
confidence: 99%